2008
DOI: 10.1634/stemcells.2008-0156
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Euploid Human Embryonic Stem Cells from Aneuploid Embryos

Abstract: Human embryonic stem cells (HESCs) are pluripotent cells derived from the inner cell mass of preimplantation embryos. In this study, to isolate new lines of HESCs, we used blastocyst-stage embryos diagnosed as aneuploid in preimplantation genetic screening (PGS). During in vitro fertilization treatments, PGS is widely applied to identify chromosomal aneuploidies, especially in cases of advanced maternal age. Embryos that are detected as carrying aneuploidies are destined to be discarded unless donated for rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 32 publications
4
54
0
1
Order By: Relevance
“…In consistent with the previous results, in which it was aimed to derive chromosomally abnormal hESC lines for investigation of various aspects of early embryonic development, all our hESC lines derived from those embryos had normal karyotypes (Munne et al, 2005;Lavon et al, 2008). As stated in these studies, this unexpected result has been suggested to self correction of embryos during long-term in vitro culture (Hazan et al, 2008;Lavon et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In consistent with the previous results, in which it was aimed to derive chromosomally abnormal hESC lines for investigation of various aspects of early embryonic development, all our hESC lines derived from those embryos had normal karyotypes (Munne et al, 2005;Lavon et al, 2008). As stated in these studies, this unexpected result has been suggested to self correction of embryos during long-term in vitro culture (Hazan et al, 2008;Lavon et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…After diagnosis, abnormal embryos were used to derive hESC lines with specific single gene mutation. In the second group of PGD cycles, embryos belonging to couples with advanced maternal age, a history of recurrent miscarriages and repeated implantation failures are destined to chromosomal screening (Kahraman et al, 2000Lavon et al, 2008;Munne et al, 2005;Verlinsky et al, 2005). Following PGD, chromosomally abnormal embryos were subjected to derivation of hESC lines having chromosomal aneuploidies.…”
Section: Source Of Supernumerary Human Embryosmentioning
confidence: 99%
“…Suss-Toby et al also reported a hESC coming from 1PN embryos with normal diploid karyotype (46, XX) [21]. However, the embryo development maybe differ from hESCs in-vitro, as suggested by Lavon et al that the mosaic could be corrected to normal karyotype in hESCs by faster proliferating of normal cells than abnormal cells during the growth of the hESCs, and then took over the culture, whereas the mosaic ICM of blastocyst only divided a few times in-vivo, which may lead to a mosaic fetus [22]. Although most of the 1PN hESCs were normal diploid, one aneuploid hESC line with trisomy 16 (47, XY, +16) was still observed.…”
Section: Discussionmentioning
confidence: 97%
“…Our observation of aneuploidy rate that increases over time supports this possibility. Lavon et al 36 demonstrated the possibility that mosaicism may lead to one cell population, by the derivation of euploid hESCs from monosomy 21 embryos, which were in fact mosaic. They detected high rate of monosomy 21 mosaicism in early passages of hESCs and concluded that in higher passages the euploid cells took over the culture.…”
Section: Aneuploidy Screeningmentioning
confidence: 99%